Comparing stressful factors among dental students pre and during COVID-19 pandemic - Faisal, Ghasak Ghazi; Al-Ani, Ali Sabri Radeef; Khaled, Mohamad F. (2022)
Introduction: COVID-19 pandemic has negatively affected higher education due to the sudden need to shift to an online mode of teaching and learning which is new to the students and lecturers. Dental students are impacted by this type of teaching and learning as a considerable portion of their curriculum requires clinical training on real patients. This study aimed to compare the stressful factor among dental students during COVID-19 pandemic with stressors assessed before the pandemic. Methods: This study was conducted among dental students during COVID-19 Movement control order where online teaching and learning were implemented. Dental students at Kulliyyah of Dentistry, International Islamic University Malaysia were given a list of possible stressful factors and were asked to rate these stressors on a scale from 0 (I don’t consider it a stressful factor/Does not apply to me) to 4 (I consider it an extreme stressor). The results were compared to the source of stressors among dental students before COVID-19 pandemic. Results: There are consistent stressors before and during COVID-19 pandemic such as ‘lack of motivation to learn’, ‘Fear of failing or unable to catch up’, ‘feeling incompetent’, ‘Fear of unemployment after graduation’ however the ranking and mean score of these stressors increased during COVID-19 pandemic. New stressors emerged during the pandemic which were ‘Understanding lecturers during online classes’, ‘Cannot catch up with online learning’, ‘Fear of not completing clinical requirements/logbook’. Conclusion: Academic related stressors consistently exist among dental students however their severity increased during COVID-19 pandemic. Academic institutions need to adopt strategies to alleviate the newly emerging stressors related to the effect of pandemic on teaching and learning